(untitled) (International journal of artificial intelligence, 2025)
In the modern economic environment, project management is considered a crucial strategic tool for enhancing business competitiveness, optimizing resource utilization, and implementing innovative solutions. The application of project management in improving business processes enables systematic analysis, clear goal setting, risk management, and performance evaluation, thereby increasing overall efficiency. This article scientifically analyzes the principles and methodologies of project management (Agile, Lean, PMBOK, PRINCE2, etc.) and their mechanisms of implementation in business processes. The results of the study demonstrate that the integration of project management in enterprises plays a significant role in digitalizing processes, improving labor productivity, and enhancing the quality of strategic decision-making. The article also emphasizes the practical application of project management in Uzbekistan and its impact on business efficiency.